Medication Reconciliation Improvement Through the Use of Video. Issue 1 (11th February 2015) - Dewan, Maya; Kraus, Blair; Davis, Daniela; McCloskey, John
Abstract: Accurate medication reconciliation at the time of hospital admission is vital to preventing adverse drug events. Compliance with medication reconciliation in our pediatric intensive care unit was low initially with overall medication reconciliation at 70%. Due to the high front line provider turnover in our unit, we focused on technological reminders for completion and used unique and innovative ways to motivate our supervising staff. Our goal was to reach >95% completion within 24 hours for medication reconciliation for all patients admitted to the pediatric intensive care unit. Pre-pilot discussions focused on examples of errors of medication reconciliation within our own institution resulting in patient harm via traditional power point presentation. The initial pilot phase instituted a job aid on how to add the medication reconciliation completion reminder column. Email updates on completion status began one week after initiation. During the implementation and spread phase, fun interactive videos were used to acknowledge roll out to the full unit. Compliance was monitored and humorous biweekly video updates emphasizing accountability were introduced. In the sustain phase, monthly video updates served as education and a reminder for provider staff. The use of a medication reconciliation completion column and reminder emails resulted in goal completion (>95%) by three weeks post intervention for the pilot unit. Overall medication reconciliation completion also reached goal of >95% completion within the entire unit after three weeks of implementation and spread. Compliance fell below goal so video updates were modified utilizing humor and emphasizing accountability. This resulted in sustained compliance now more than forty weeks post implementation. Unit compliance currently remains >95% completion within 24 hours now more than forty weeks post intervention. The use of the medication reconciliation reminder column resulted in improvement in compliance; however, that improvement was not sustained. The addition of humorous videos highlighting accountability allowed for sustained improvements.